Tectono-Sedimentary evolution and provenance shifts of Cenozoic sub-basins in the Central Myanmar Basin, Myanmar - Mengying He; Hongbo Zheng; Yun Hu; Huan Xu; Peter D. Clift; Bihui Zhang; Tin Aung Myint (Journal of Asian Earth Sciences, 2026)

Sedimentary records of silicate weathering on the continental shelf of the South Yellow Sea during glacial periods - Jin Zhang; Shiming Wan; Yifei Yang; Shouye Yang; Peter D. Clift; Yulong Guo; Debo Zhao; Yi Tang; Zhaojie Yu; Zehua Song; Zhongjing Cheng; Zaibao Yang; et al. (Science China Earth Sciences, 2026)

Climatic and anthropogenic controls on late Holocene sediment transport to the Gulf of Mexico by the Mississippi River - Peter D. Clift; Bailey Wycoff; Andrew Carter; Samuel Muñoz; Nikki Neubeck; Brittney Gregory; Carol A. Wilson; Tammy Rittenour; Jerzy Blusztajn; Tamer Ali (Earth-Science Reviews, 2026)

High-resolution marine records of human-nature interactions in the Yellow River Basin since 2.2 kyr ago - Wenqiang Pei; Shiming Wan; Peter D. Clift; Jin Zhang; J. Paul Liu; Yongming Han; Debo Zhao; Zhendong Luan; Zhaojie Yu; Zehua Song; Anchun Li (Global and Planetary Change, 2026)

Impacts of Qinling Mountains Elevation on Precipitation in Central China: A WRF Modelling Analysis - Bin Wang; Yiru Yang; Peter Clift; Wenting Gao; Li Xing; Yurui Zhang; Chris Brierley; Ting Sun; Hui Tang; Wei Shang; Ying Cheng; Shuangshuang Li; et al. (International Journal of Climatology, 2025)
The tectonically driven uplift of the Qinling Mountains during the Cenozoic may have resulted in significant climatic and environmental effects, but this remains poorly understood. This study investigates the influence of the Qinling Mountains' uplift on summer precipitation patterns in central China using the Weather Research and Forecasting (WRF) model to design topographic sensitivity experiments. The results show that the uplift of the Qinling Mountains leads to the intensification of the spatial distribution of precipitation in China, with increased precipitation in the south and decreased precipitation in the north. The uplift of the Qinling Mountains from an average elevation of 400 m to their current elevation results in a 13% (64.3 mm) decrease in precipitation north of the Qinling Mountains, a 39% (134.4 mm) increase in the Qinling Mountains, and a 1.5% (8.1 mm) increase to the south. In particular, precipitation in the Loess Plateau decreased by 62.7 mm (18%). As the Qinling Mountains uplift, the physical barrier effect is enhanced, leading to a reduction in water vapour over the Qinling Mountains. However, the forced uplift of air masses results in enhanced vertical motion, which in turn increases summer precipitation over the Qinling Mountains. In contrast, although water vapour accumulation occurs to the north of the Qinling Mountains, the absence of topographic forcing leads to decreased precipitation. When the Qinling Mountains uplifted to an average elevation of 1600 m, they began to exert a more pronounced blocking effect on wind and water vapour transport. This elevation effectively transformed the Qinling Mountains into a natural barrier, further separating the climatic regimes of the north and south of China. These findings indicate that the changes in elevation during the uplift of the Qinling Mountains have had a marked impact on the spatial distribution of precipitation in the central China.

Source-to-sink system in the Paleogene Raoyang Sag, Bohai Bay Basin, China: Insights into the evolution of the East Taihang Mountain range - Yifan Du; Peter D. Clift; Hehe Chen; Qiwei Gou; Linglong Li; Xiaomin Zhu (Journal of Asian Earth Sciences, 2025)

Evolution of silicate weathering in the Yangtze River Basin since 3.5 Ma as archived in the East China Seas: Controlling factors and global significance - Jin Zhang; Shiming Wan; Peter D. Clift; Hualong Jin; Zehua Song; Yi Tang; Zhaojie Yu; Kaidi Zhang; Jian Lu; Wenjun Jiao; Anchun Li (Global and Planetary Change, 2025)

Evolutionary Triggers of Plant Speciation in the Himalaya‐Tibet‐Hengduan Biodiversity Epicentre - Maharaj K. Pandit; Kumar Manish; Sandeep Sen; Kamaljit S. Bawa; Andrew H. Knoll; A. Alexander G. Webb; Peter D. Clift; Fabien L. Condamine; Carina Hoorn (Journal of Biogeography, 2025)
Background Past studies linking geologic and climatic controls on speciation in the Himalaya, Tibet and Hengduan (HTH) regions do not fully capture the mechanisms underlying patterns of plant diversity and endemism in hyperdiverse mountain ecosystems. Aims This study sheds new light on the orogenic and climatic drivers of plant endemism and diversity in the HTH region and unravels the mechanisms behind plant speciation and assembly. Materials & Methods We re‐examine the past findings on geo‐climatic controls on speciation in the HTH. We also analyse new datasets on the elevational patterns of endemic species richness in the HTH regions and correlate these with the hypsometric profiles based on digital elevation models of these regions. Results We discover that the phased evolution of HTH mountain‐building and climate oscillations, and species radiations were not exactly synchronous, but were interspersed with periods of inactivity. We find an inverse yet overlapping relationship between elevation‐area troughs (EATs) of hypsometric profiles and peaks of endemic plant richness in the HTH, indicating that most endemic species occupy the higher elevational belts with the least geographic areas. These elevational belts comprise geographically and biologically isolated habitats. Discussion and Conclusions We infer that orogeny, monsoon and glaciations have shaped the highly dissected HTH landscapes, characterised by high‐relief topography, leading to population isolation, speciation and endemism, albeit with temporal lags. Glacial–interglacial cycles have further promoted isolation, co‐habitation, hybridisation and polyploidy among plant populations, generating and accelerating endemic radiations. Our results provide crucial evidence linking mountain‐building, climatic events and landform development with plant species richness and endemism in the HTH regions and potentially in other mountain ecosystems.

Fossil diatoms and their significance for paleoenvironment construction on the shelf of Northern South China Sea - Jinpeng Zhang; Yingzhi Ren; Chong Sheng; Peter D. Clift; Bin Yang; Dehao Xie; Jinwei Zhang; Taihao Chen; Shengzhong Ma; Ningfeng Zeng; Yanbiao Chen; Yaohong Shi; et al. (Geo-Marine Letters, 2025)

Molybdenum isotopic evidence for linked changes in North Pacific Intermediate Water and subtropical Northwest Pacific redox conditions over the last 200 k.y - Yanguang Dou; Chenghui Sun; Shouye Yang; Xuefa Shi; Yonghua Wu; Jingyi Cong; Yong Zhang; Fengmei Wang; Feng Cai; Peter D. Clift (Global and Planetary Change, 2025)

Provenance shift of the abyssal plains in the Southwest sub-basin of the South China Sea at ∼ 8 Ma: Tectonics & climate changes implication - Yi Yan; Lan Liu; Peter D. Clift; Yildirim Dilek; Anbei He (Marine Geology, 2024)

History of human activity in South China since 7 cal ka BP: Evidence from a sediment record in the South China Sea - Mengshan Ju; Shiming Wan; Peter D. Clift; Wenqiang Pei; Dongfeng Jiao; Jin Zhang; Wenjun Jiao; Debo Zhao; Zhaojie Yu; Zehua Song; Anchun Li (Quaternary Science Reviews, 2024)

Contribution of Asian dust into the sediment budget of the Parece Vela Basin over the last 1 Ma: Implications for the climate change in East Asia - Yongqiang Sun; Yi Yan; Peter D. Clift; Yildirim Dilek; Qi Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The impact of Himalayan-Tibetan erosion on silicate weathering and organic carbon burial - Peter D. Clift; Tara N. Jonell; Yifan Du; Thomas Bornholdt (Chemical Geology, 2024)

Competing influence of the Taiwan orogen and East Asian Summer Monsoon on South China Sea paleoenvironmental proxy records - Amy I. Hsieh; Shahin E. Dashtgard; Peter D. Clift; Li Lo; Romain Vaucher; Ludvig Löwemark (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Climatic influence on sediment distribution and transport in the Thar Desert (Sindh and Cholistan, Pakistan) - Muhammad Usman; Peter D. Clift; Guido Pastore; Giovanni Vezzoli; Sergio Andò; Marta Barbarano; Pieter Vermeesch; Eduardo Garzanti (Earth-Science Reviews, 2024)

Cretaceous long-distance lithospheric extension and surface response in South China - Jianhua Li; Shuwen Dong; Peter A. Cawood; Hans Thybo; Peter D. Clift; Stephen T. Johnston; Guochun Zhao; Yueqiao Zhang (Earth-Science Reviews, 2023)

Farming stimulated stronger chemical weathering in South China since 3.0 ka BP - Wenqiang Pei; Shiming Wan; Peter D. Clift; Guanqiang Cai; Debo Zhao; Jin Zhang; Wenjun Jiao; Mengshan Ju; Zehua Song; Anchun Li (Quaternary Science Reviews, 2023)

Sedimentary budget of the Northwest Sub-basin, South China Sea: controlling factors and geological implications - Yanmei Wu; Weiwei Ding; Peter D. Clift; Jiabiao Li; Shaoru Yin; Yinxia Fang; Hanghang Ding (International Geology Review, 2020)

Starting a New Ocean and Stopping It - Chun-Feng Li; Peter Clift; Zhen Sun; Hans Christian Larsen (Oceanography, 2019)

Tectonic controls of the onset of aeolian deposits in Chinese Loess Plateau – a preliminary hypothesis - Bin Wang; Anu Kaakinen; Peter D. Clift (International Geology Review, 2018)

Ground-penetrating radar study of beach-ridge deposits in Huangqihai Lake, North China: the imprint of washover processes - Xin Shan; Xinghe Yu; Peter D. Clift; Chengpeng Tan; Shunli Li; Zhixing Wang; Dongxu Su (Frontiers of Earth Science, 2016)

A sediment budget for the Transkei Basin, Southwest Indian Ocean - Gabriele Uenzelmann-Neben; Peter D. Clift (Marine Geophysical Research, 2015)

Introduction to special collection on geology, tectonics and hydrocarbon systems of SE Asia - Peter D. Clift; Zhen Sun (Marine Geophysical Research, 2013)

The sedimentary, magmatic and tectonic evolution of the southwestern South China Sea revealed by seismic stratigraphic analysis - Lu Li; Peter D. Clift; Hung The Nguyen (Marine Geophysical Research, 2013)

J. P. Terry and J. Goff: Natural hazards in the Asia–Pacific region - Peter Clift (Marine Geophysical Research, 2013)

Impacts of sediment supply and local tectonics on clinoform distribution: the seismic stratigraphy of the mid Pleistocene-Holocene Indus Shelf - David R. Limmer; Timothy J. Henstock; Liviu Giosan; Camilo Ponton; Ali R. Tabrez; David I. M. Macdonald; Peter D. Clift (Marine Geophysical Research, 2012)

Macroscopic to microscopic scales of particle dosimetry: from source to fate in the body - Paul A. Solomon; Peter Gehr; Deborah H. Bennett; Robert F. Phalen; Loyda B. Méndez; Barbara Rothen-Rutishauser; Martin Clift; Christina Brandenberger; Christian Mühlfeld (Air Quality, Atmosphere & Health, 2012)

Nanotoxicology: a perspective and discussion of whether or not in vitro testing is a valid alternative - Martin J. D. Clift; Peter Gehr; Barbara Rothen-Rutishauser (Archives of Toxicology, 2011)

Editorial for MGR - Peter Clift (Marine Geophysical Research, 2009)

Geochemical evolution of the Dras–Kohistan Arc during collision with Eurasia: Evidence from the Ladakh Himalaya, India - PETER D. CLIFT; ROBYN HANNIGAN; JERZY BLUSZTAJN; AMY E. DRAUT (Island Arc, 2002)
The Dras 1 Volcanic Formation of the Ladakh Himalaya, India, represents the eastern, upper crustal equivalent of the lower crustal gabbros and mantle peridotites of the Kohistan Arc exposed in Pakistan. Together these form a Cretaceous intraoceanic arc now located within the Indus Suture zone between India and Eurasia. During the Late Cretaceous, the Dras–Kohistan Arc, which was located above a north‐dipping subduction zone, collided with the south‐facing active margin of Eurasia, resulting in a switch from oceanic to continental arc volcanism. In the present study we analyzed samples from the pre‐collisional Dras 1 Volcanic Formation and the postcollisional Kardung Volcanic Formation for a suite of trace elements and Nd isotopes. The Kardung Volcanic Formation shows more pronounced light rare earth element enrichment, higher Th/La and lower ɛ Nd values compared with the Dras 1 Volcanic Formation. These differences are consistent with an increase in the reworking of the continental crust by sediment subduction through the arc after collision. As little as 20% of the Nd in the Dras 1 Volcanic Formation might be provided by sources such as the Karakoram, while approximately 45% of the Nd in the Kardung Volcanic Formation is from this source. However, even before collision, the Dras–Kohistan Arc shows geochemical evidence for more continental sediment contamination than is seen in modern western Pacific arcs, implying its relative proximity to the Eurasian landmass. Comparison of the lava chemistry in the Dras–Kohistan Arc with that in the forearc turbidites suggests that these sediments are partially postcollisional, Jurutze Formation and not all pre‐collisional Nindam Formation. Thus, the Dras–Eurasia collision can be dated as Turonian–Santonian (83.5–93.5 Ma), older than it was previously considered to be, but consistent with radiometric ages from Kohistan.

The stratigraphic evolution of the Indus Fan and the history of sedimentation in the Arabian Sea - Peter Clift; Christoph Gaedicke; Rosemary Edwards; Jae Il Lee; Peter Hildebrand; Shahid Amjad; Robert S. White; Hans-Ulrich Schlüter (Marine Geophysical Research, 2002)